Diet replacement with whole insect larvae affects intestinal morphology and microbiota of broiler chickens - Stylianos Vasilopoulos; Ilias Giannenas; Ifigeneia Mellidou; Ioanna Stylianaki; Efthimia Antonopoulou; Athina Tzora; Ioannis Skoufos; Christos G. Athanassiou; Elias Papadopoulos; Paschalis Fortomaris (Scientific Reports, 2024)
Abstract Insect-based diets are gaining interest as potential ingredients in improving poultry gut health. This study assessed the dietary treatment with whole dried Tenebrio molitor larvae (TM) on broiler chickens’ gut microbiota and morphology. 120 Ross-308 broilers received treated diets with 5% (TM5) and 10% (TM10) replacement ratio in a 35-day trial. Intestinal histomorphometry was assessed, as well as claudin-3 expression pattern and ileal and caecal digesta for microbial community diversity. Null hypothesis was tested with two-way ANOVA considering the intestinal segment and diet as main factors. The TM5 group presented higher villi in the duodenum and ileum compared to the other two (P < 0.001), while treated groups showed shallower crypts in the duodenum (P < 0.001) and deeper in the jejunum and ileum than the control (P < 0.001). Treatments increased the caecal Firmicutes/Bacteroidetes ratio and led to significant changes at the genus level. While Lactobacilli survived in the caecum, a significant reduction was evident in the ileum of both groups, mainly owed to L. aviarius. Staphylococci and Methanobrevibacter significantly increased in the ileum of the TM5 group. Results suggest that dietary supplementation with whole dried TM larvae has no adverse effect on the intestinal epithelium formation and positively affects bacterial population richness and diversity.